The Englishized Subject Postcolonial Writings in Hong Kong, Singapore and Malaysia - Tam, Kwok-kan (Springer Nature Singapore : Imprint: Springer, 2019)
This book addresses issues of how the cultures in Hong Kong, Singapore and Malaysia have been Englishized in postcolonial and globcalized contexts, not just in terms of language, but also in writers'/people's subjectivity. Taking a cultural-literary approach to the study of Englishized subjectivity, the book offers a unique study of hybridized literary/language forms by relating them to bilingual thinking and bicultural sensibility. Poets, novelists and playwrights have different strategies to cope with new images and new forms of expression that can capture their sense of hybridized identity, and as a result, hybridity becomes creativity.